PENGARUH KEGIATAN PENGOLAHAN SAMPAH DI SEKOLAH TERHADAP PRILAKU PEDULI LINGKUNGAN SISWA KELAS VI PADA MATA PELAJARAN PKN DI SDN NO . 9 ACEH SELATAN - Julissasman; T Cut Lizam (LPPM Universitas Cipta Mandiri, 2025)
The school environment is a place or forum for children to be guided in all aspects, morals, knowledge, and skills are very important things to be fostered in the school environment, so not only knowledge is prioritized but more so to form character and instill moral values ​​​​in the children who are in the school environment and of course all of that cannot be separated from the role of educators in the school environment. The purpose of this study was to analyze the influence of waste management activities in schools on the environmental care behavior of 36 sixth grade students in the Civics subject of SD Negeri No. 9 Tapaktuan, South Aceh Regency. The sampling technique used a minimum sample and used the proportional random sampling method. The instruments used were questionnaires and observation sheets. Primary data were obtained through interviews and observations while secondary data from SDN No. 9 Tapaktuan. Data analysis used the chi-square test with = 0.05. From the results of the study, it was found that the level of student knowledge about the influence of waste management activities in schools on the environmental care behavior of sixth grade students in the Civics subject at SDN No. 9 South Aceh, 50% had insufficient knowledge, 19.5% had sufficient knowledge, and only 30.5% had good knowledge. Meanwhile, 70% of respondents had negative attitudes, only 30% had positive attitudes. 55% of respondents littered and 45% disposed of trash properly. The results showed a moderate correlation between knowledge and environmentally responsible waste disposal behavior. Similarly, education (Civics learning) and environmental care attitudes and behaviors had a moderate correlation. The conclusion of this study is that there is a correlation between education (Civics learning) and attitudes and student behavior. Suggestions include maintaining environmental cleanliness and providing trash bins to ensure a healthy and litter-free environment.